Carcinoma basaloide - Escamoseo de cebeça: relato de 4 casos - Tagliarini, José Vicente [UNESP]; Castilho, E. C. [UNESP]; Bacchi, C. E. [UNESP]; Cortez Montovani, J. [UNESP] (My University, 1997)
Basaloid squamous carcinoma is an aggressive subtype of squamous carcinoma of superior aerodigestive tract. This tumor has been recently described and it seems to have higher incidence in tongue, hypopharynx and supraglottis. It has more agressive biological behavior than pure type of squamous cell carcinoma. We report 4 cases of this tumor and we present a review of the literature.
Basaloid squamous carcinoma: report of 4 cases
Keywords: basaloid squamous carcinoma; adult; aged; case report; histopathology; human; human tissue; larynx carcinoma; male; squamous cell carcinoma; tongue carcinoma